(untitled) (Global Journal of Science Frontier Research, 2017)
Near to 99.99 percent of sheep breeds in southern region is in the traditional way, in which indigenous breeds and types predominate. Indigenous sheep genetic improvement via 50% Dorper crossed ram introduction and community based sheep breed improvement, are found mostly under taken by southern agricultural research centre.50% Dorper crossed ram, Bonga and doygena ram were widely distributed to different agroecology of the region. The objective of this paper is to assess the productive performance of introduced ram based farmer perceptions and to analyze performance of the introduced breeding ram in Damot sore and Merab Badewacho worda southern Ethiopia. Community based improved Doygena ram were preferred for their ability to produce multiple birth, for its attractive coat color, its resistance to health problem in Damot sore while in Merab Badewacho the breed perform less significant.